Enriching the methanol generation via CO2 photoconversion over the cockscomb-like fibrous silica copper - Mahadi, Bahari; Che Rozid, Mamat; Aishah, Abdul Jalil; Shing, Lo Sook; Nurul Sahida, Hassan; F. F.A., Aziz; Alhassan, Mansur; Mohd Ghazali, Mohd Nawawi; Kamarizan, Kidam; Herma Dina, Setiabudi (Elsevier Ltd, 2022)
Carbon dioxide (CO2) photoconversion into methanol (CH3OH) was recognized as a beneficial approach to overcoming future energy and environmental issues. Here, CO2 photoconversion into CH3OH was intensively evaluated over fibrous silica-copper (FSCu) and copper-supported fibrous silica (CuO/KCC-1) generated through a microemulsion and incipient wetness impregnation approach, respectively. The physicochemical attributes of the generated photocatalysts were characterized via UV–vis spectroscopy, X-ray diffraction, N2 physisorption, Field-emission scanning electron microscopy, and Fourier-transform infrared spectroscopy analysis. Depiction of the characterization results revealed that FSCu possessed a considerable surface area (299.7 m2 g−1) as well as pore volume (0.70 cm3 g−1) than those of CuO/KCC-1 and CuO. Indeed, the excellent CuO dispersion and intense CuO-interaction resulted from the alternately aligned CuO and SiO2 in the fibrous framework. As a result of these great attributes, the FSCu photocatalyst recorded a superior yield of CH3OH (412.4 µmol gcat−1 h−1) with triethylamine assistance as a sacrificial reductant, followed by CuO (310.3 µmol gcat−1 h−1) and CuO/KCC-1 (189.6 µmol gcat−1 h−1). Additionally, the ideal bandgap position for FSCu compared to CuO/KCC-1 contributed to the greater yield of CH3OH. The parameter evaluations recorded that the highest yield of CH3OH for FSCu was acquired at a catalyst of 0.6 g L−1, 100 mL min−1 of CO2, and the amount of TEA of about 50 mL. This paper also proposes a photoconversion mechanism for synthesized photocatalysts, as well as a comparative assessment of their performance with recently developed CuO-based photocatalysts.